Economic Valuation of the Development and Maintenance of Merdeka Square in Malang City and Merjosari Park Using a Use Value Approach and Cost Benefit Analysis Method - Abdurrahman Muhyiddin; Farida Rahmawati (JURNAL ECONOMINA, 2026)
Urban green open spaces (RTH) play a crucial role in supporting ecological balance and socio-economic development in rapidly growing cities. This study aims to analyze and compare the economic benefits of Alun-Alun Merdeka Malang City and Merjosari Park, and to evaluate whether the government’s development and maintenance costs are commensurate with the long-term benefits received by the community. This research employs a quantitative approach using the Cost-Benefit Analysis (CBA) method, incorporating Net Present Value (NPV), Benefit-Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period (PP) with a 5% discount rate. Primary data were collected through the Contingent Valuation Method (CVM) using a dichotomous choice approach to estimate Willingness to Pay (WTP), and analyzed using binary logistic regression. The results indicate that both RTH locations are economically feasible, with positive NPV, BCR > 1, and IRR exceeding the discount rate. Although the difference in WTP is relatively small (1.77%), Alun-Alun Merdeka generates approximately 205% higher total economic benefits due to having around 200% more visitors. Its IRR (34.32%) is significantly higher than Merjosari Park (8.93%), with a faster payback period. These findings imply that while all RTH investments are economically viable, city-scale green spaces yield higher economic returns, whereas neighborhood-scale parks remain essential for ensuring equitable social and environmental benefits.